PENGARUH FAKTOR INTERNAL TERHADAP KREDIT BANK YANG TERDAFTAR DI BEI (Students' Journal of Accounting and Banking, 2013)
The objective of this research is to analyze the effect of variable Third Party Fund(TPF),Capital Adequacy Ratio (CAR), Return on Asset (ROA) and Non Performing Loan (NPL) to the volume of credit in bank listed in BEI. The populations used in this research are all of the listed banking in Indonesian Stock Exchange is the financial statements, annual report, and ICMD during the years 2008-2011, and to importance the research used in sample with the method “purpose sampling”. So that, the result is 24 companies appropriate with the criteria. The research method used in multiple regression analysis. The company data used normality, multicollinearity, autocorrelation, and heteroscedasticity. Based on the partial test result to bank in BEI indicates that the variable TPF have positive effect and significant to the volume of credit. In addition, the variable CAR has negative influence and significant to the volume of credit, then ROA has positive influence and no significant to the volume of credit and the last is NPL has positive effect and significant to the volume of credit. Keywords: Volume of Credit, TPF, CAR, ROA, NPL